Prevalence of obesity and its risk factors in school going adolescents of urban Bangalore, India - S., Vedavathy; Kamath, Ganesh; Sangamesh, . (International Journal of Contemporary Pediatrics, 2016)
Background: Obesity, one of the most widespread and major problems affecting children and adolescents is of global nutritional concern. In last two decades, the prevalence of obesity has doubled in children and tripled in adolescents in United States of America. There is not enough data on the prevalence of obesity in adolescents in urban Bangalore. Hence the present study aims to fulfil this urgent requirement. Aims & objectives of the study were to study the prevalence of obesity and its risk factors in school going adolescents of urban Bangalore. Methods: Observational study conducted in adolescents between the ages 11 to 19 years from the schools around Indira Gandhi Institute of Child Health, Bangalore. Results: The maximum number of adolescents in the present study belonged to the 14 years age group. Majority of the adolescents studied had a birth weight of 2.5 to 3.5 kg. 6.7% of the total adolescents had history of sleep disturbance. There was family history of hypertension in 19.4%, diabetes mellitus in 8.7%, obesity in 9.9% and cardiovascular diseases in 1.1% of the adolescents. The prevalence of obesity was 5.9%. Conclusions: The overall prevalence of obesity is 5.9%, 4.2% girls and 6.9% boys are obese. Obese children were more likely to belong to higher socioeconomic strata; more obese children had mixed diet. Family histories of hypertension, obesity and diabetes mellitus were significant risk factors. Sleep disturbance was associated with obesity.